Evaluation of teachers of the first three grades for the role of the reading and arithmetic initiative (RAMP) in developing students’ reading skills "A field study in the schools of the Northwestern Badia District" - البري احلام (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This study aimed to explore the role of the Ramp reading and Mathematics initiative in developing some of reading skills among students of the first three grades from the point of view of stage teachers in the Northwestern Badia district, and to study the impact of the variables of teaching experience, educational qualification, and gender. The study adopted the descriptive approach and the researcher used a questionnaire consisting of (16 paragraphs) divided into (4) domains as a tool. It was distributed to a random sample of (30) male teachers and (270) female teachers from all stage teachers in the northwestern Badia district schools in Jordan. The results of the study showed that: 1- The role of the reading and Mathematics initiative in developing the reading skills of the students of the first three grades was (high). 2- There are statistically significant differences attributed to the gender variable in favor of females, and there are differences attributed to the teaching experience variable in favor of experience from (1-7) years, and that there are no statistically significant differences at the level (α≥0.05) Of significance attributed to the educational qualification variable.